Digital Content Marketing in Brand Management of Small Business Enterprises, Trading Companies and Territorial Marketing - USTIK, Tetiana; DUBOVYK, Tetiana; LAGODIIENKO, Volodymyr; CHERNOBROVKINA, Svitlana; VLASENKO, Yurii; SHMATOK, Maksym (Theoretical and Practical Research in Economic Fields; Vol 15 No 3 (2024): TPREF, Volume XV, Issue 3(31), Fall 2024, 2024)
Purpose: The research aims at a practical evaluation of the influence of digital content marketing in the system of brand management on the examples of small businesses, trading companies and territorial marketing. Methodology: To achieve the aim, the See-Think-Do-Care strategy was used, and a matrix of correlation of digital content and the object of realisation of digital content marketing in brand management was developed. Mathematical methods such as correlation analysis and regression analysis were used as well. Findings: The results of the study demonstrated that the type of digital content management is affected by the size and activity kind of the company, enterprise or organisation, which proves the necessity for diverse digital content. Correlation analysis enabled the proof of a tight correlation (0,98) between digital content marketing and brand management. A parameter indicating the influence of digital content marketing, was found to be expenses for digital content marketing. The parameter, illustrating the efficiency of brand management for small businesses and trading companies was determined to be average annual income, and for territorial marketing - number of tourists per year. Three types of models were built to determine the quantitative influence of digital marketing on brand management. The results of Model 1 have the most significant effect as the influence of digital content marketing on income increase, and thus, brand development amounts to from 8324 USD to 13571 USD. While talking about Model 2, income increase fluctuates from 3030 USD to 3600 USD per year. Evaluation results on Model 3 illustrate the insignificant influence of digital content marketing on income and brand management. Originality: In further studies, it is proposed to divide small businesses based on activity kinds and study digital content marketing in brand management depending on activity kinds.